Lobbying on the integrated reporting framework: An analysis of comment letters to the 2011 discussion paper of the IIRC. Issue 3 (16th March 2015) - Reuter, Marek; Messner, Martin
Abstract : Purpose: – The purpose of this paper is to examine formal participation in the early phase of the International Integrated Reporting Council's (IIRC's) standard-setting. The objective of the paper is to shed light on the characteristics of lobbying parties and the determinants of their lobbying behavior toward the IIRC. Additionally, the most important points of contestation regarding the IIRC's initial proposal for integrated reporting are identified and discussed. Design/methodology/approach: – The authors analyze comment letters issued toward the IIRC's 2011 discussion paper on the basis of a content analysis. The analysis is guided mainly by Sutton's (1984) rational-choice model of lobbying and by findings from extant financial accounting lobbying research. The analysis of the data is both quantitative and qualitative. Findings: – The paper improves the understanding of the political nature of standard-setting in the context of integrated reporting. Among other things, the authors find that comment letters toward the IIRC's discussion paper are mainly written by large multinational firms (as opposed to small- and medium-sized ones) and by preparers (as opposed to users). The authors also observe active lobbying by sustainability service firms and professional bodies which tend to take a critical position vis-à-vis the discussion paper's emphasis on investor needs and shareholder value creation. Moreover, the qualitative analysis reveals that respondents voice different concerns regarding, for instance, the scope of audience of integrated reporting, issues of materiality and the relationship between integrated reporting and other existing reporting frameworks. Research limitations/implications: – The analysis is limited to a consideration of the 2011 discussion paper of the IIRC. The IIRC's more recent and forthcoming proposals will likely provide a basis to extend the paper's findings and allow investigation of the role of lobbying for the further development of the framework. Originality/value: – The paper is, to the best of the knowledge, the first one to explore lobbying behavior by means of comment letters in the context of integrated reporting.